Pengaruh e-commerce dan sistem informasi akuntansi terhadap efektivitas kinerja keuangan pada pelaku UMKM di Tangerang - Yuscintara, Brigita Andriana; Hendrani, Ai (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aims to analyze the effect of e-commerce and accounting information systems on the effectiveness of financial performance of UMKM in Tangerang. The population used in the study was UMKM in the Tangerang area by taking a sample of 157 UMKM using the purposive sampling method with the criteria of UMKM selling using e-commerce for at least 1 (one) year, operating in the Tangerang area and using accounting applications for financial records such as cash books, quickbooks, wave, Jubelio, and more. The type of data is primary data sourced from the results of questionnaires that have been distributed via google form to UMKM. The data analysis method used in this study is the Normality Test, Classical Assumption Test, Multiple Linear Regression Test, t-test, and f-test). The results of this study indicate that simultaneously e-commerce and accounting information systems affect the effectiveness of company performance. Partially, e-commerce has a positive effect on the effectiveness of financial performance, besides that the financial information system has a positive effect on the effectiveness of financial performance.